Treatment Options for Abdominal Rectus Diastasis - Jessen, Majken Lyhne; Öberg, Stina; Rosenberg, Jacob (Frontiers in Surgery, 2019)
Background Abdominal rectus diastasis is a condition where the abdominal muscles are separated by an abnormal distance due to widening of the linea alba causing the abdominal content to bulge. It is commonly acquired in pregnancies and with larger weight gains. Even though many patients suffer from the condition, treatment options are poorly investigated including the effect of physiotherapy and surgical treatment. The symptoms include pain and discomfort in the abdomen, musculoskeletal and urogynecological problems in addition to negative body image and impaired quality of life. The purpose of this review was to give an overview of treatment options for abdominal rectus diastasis. Results The first treatment step is physiotherapy. However, evidence is lacking on which regimen to use and success rates are not stated. The next step is surgery, either open or laparoscopic, and both surgical approaches have high success rates. The surgical approach includes different plication techniques. The recurrence and complication rates are low, complications are minor, and repair improves low back pain, urinary incontinence, and quality of life. Robotic assisted surgery might become a possibility in the near future, but data are still lacking. Conclusions Evidence on what conservatory treatment to use is sparse, and more research needs to be done. Both open and laparoscopic surgery have shown positive results. Innovative treatment by robotic assisted laparoscopic surgery has potential, however, more research needs to be done in this area as well. An international guideline for the treatment of rectus diastasis could be beneficial for patients and clinicians.